Contact resistance reduction of ZnO thin film transistors (TFTs) with saw-shaped electrode. (5th June 2018) - Park, Woojin; Shaikh, Sohail F; Min, Jung-Wook; Lee, Sang Kyung; Lee, Byoung Hun; Hussain, Muhammad M
Abstract: We report on a saw-shaped electrode architecture ZnO thin film transistor (TFT), which effectively increases the channel width. The contact line of the saw-shaped electrode is almost twice as long at the contact metal/ZnO channel junction. We experimentally observed an enhancement in the output drive current by 50% and a reduction in the contact resistance by over 50%, when compared to a typically shaped electrode ZnO TFT consuming the same chip area. This performance enhancement is attributed to the extension of the channel width. This technique can contribute to device performance enhancement, and in particular reduce the contact resistance, which is a serious challenge.